Pilot testing for long-term impact of glycerol-induced acute kidney injury on oxalate homeostasis in rats - Natalia Stepanova; Ganna Tolstanova; Iryna Akulenko; Valentyn Nepomnyashchyi; Svitlana Savchenko; Alexander Zholos; Mykola Kolesnyk (Ukrainian Journal of Nephrology and Dialysis, 2022)
Abstract. There is a general lack of research on the long-term effects of acute kidney injury (AKI) on oxalate-degrading bacteria (ODB) and their total oxalate-degrading activity (ODA) in fecal microbiota. In the present pilot study, we separately evaluated the changes in the ODB number and their total ODA in fecal microbiota at 3-time points after glycerol-induced AKI. In addition, we assessed the interactions between AKI-induced renal histopathological changes and ODB, total fecal ODA, and plasma and urine oxalate concentrations in rats.Methods. The male Wistar rats (200-300 g, n = 20) on oxalate-free diet were randomly divided into 2 groups. After 24-h of water deprivation, experimental group 1 (n = 10) received an intramuscular injection of 50% glycerol (10 ml/kg of body weight), and group 2 (n = 10) served as a control. The numbers of ODB (incubated in a highly selective Oxalate Medium and determined using the culture method), total fecal ODA and urinary oxalate (UOx) excretion were measured after injection on days 8, 22 and 70. The method of redoximetric titration with a KMnO4 solution was adopted to evaluate total ODA in fecal microbiota. Renal injury was assessed by histopathology examination, serum creatinine plasma oxalic acid (POx) concentration and daily proteinuria levels after removing the animals from the experiment on day 70.Results. After glycerol injection on days 8 and 22, no differences were found in the numbers of ODB, their total fecal ODA, and UOx excretion level between the experimental and control groups. However, after AKI initiation on day 70, the numbers of ODB, total fecal ODA, and daily UOx excretion were significantly lower in the experimental group as compared with the control group. In addition, in 10 weeks following AKI, the number of ODB had a direct correlation with UOx excretion and an inverse correlation with POx and serum creatinine concentrations and daily proteinuria. Total ODA in fecal microbiota was directly associated with the percentage of renal interstitial fibrosis and the average glomerular volumes in the experimental rats.Conclusions: AKI had long-term negative effects on the quantitative and qualitative characteristics of ODB in fecal microbiota in rats. Moreover, the results of our study confirmed an increasing trend in total fecal ODA according to the aggravation of renal interstitial fibrosis and glomerular volume in rats’ kidneys. Further studies are warranted to gain more insight into the mechanism of oxalate homeostasis impairment in AKI.